Protective Efficacy of Plasmodium vivax Radiation-Attenuated Sporozoites in Colombian Volunteers: A Randomized Controlled Trial. - Myriam Arévalo-Herrera; Juan M Vásquez-Jiménez; Mary Lopez-Perez; Andrés F Vallejo; Andrés B Amado-Garavito; Nora Céspedes; Angélica Castellanos; Karen Molina; Johanna Trejos; José Oñate; Judith E Epstein; Thomas L Richie; et al. (Public Library of Science (PLoS), 2016)
Immunizing human volunteers by mosquito bite with radiation-attenuated Plasmodium falciparum sporozoites (RAS) results in high-level protection against infection. Only two volunteers have been similarly immunized with P. vivax (Pv) RAS, and both were protected. A phase 2 controlled clinical trial was conducted to assess the safety and protective efficacy of PvRAS immunization.A randomized, single-blinded trial was conducted. Duffy positive (Fy+; Pv susceptible) individuals were enrolled: 14 received bites from irradiated (150 ± 10 cGy) Pv-infected Anopheles mosquitoes (RAS) and 7 from non-irradiated non-infected mosquitoes (Ctl). An additional group of seven Fy- (Pv refractory) volunteers was immunized with bites from non-irradiated Pv-infected mosquitoes. A total of seven immunizations were carried out at mean intervals of nine weeks. Eight weeks after last immunization, a controlled human malaria infection (CHMI) with non-irradiated Pv-infected mosquitoes was performed. Nineteen volunteers completed seven immunizations (12 RAS, 2 Ctl, and 5 Fy-) and received a CHMI. Five of 12 (42%) RAS volunteers were protected (receiving a median of 434 infective bites) compared with 0/2 Ctl. None of the Fy- volunteers developed infection by the seventh immunization or after CHMI. All non-protected volunteers developed symptoms 8-13 days after CHMI with a mean pre-patent period of 12.8 days. No serious adverse events related to the immunizations were observed. Specific IgG1 anti-PvCS response was associated with protection.Immunization with PvRAS was safe, immunogenic, and induced sterile immunity in 42% of the Fy+ volunteers. Moreover, Fy- volunteers were refractory to Pv malaria.Identifier: NCT01082341.